2018
DOI: 10.1080/13545701.2018.1442582
|View full text |Cite
|
Sign up to set email alerts
|

Introducing the Historical Gender Equality Index

Abstract: Despite recent progress, women are still disadvantaged by their greater domestic labor commitments and impaired access to well-paid jobs; and, in extreme cases, denied the right to live. This has consequences for the wellbeing of individuals and economic development. Although tools to evaluate country performance in gender equality, especially composite indicators, have been developed since the 1990s, a historical perspective is lacking. This study introduces a composite index of gender equality covering 129 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 68 publications
0
34
0
1
Order By: Relevance
“…Extending this line of research to a historical period, Perrin (2014) proposed a first attempt to measure the size of the gender gap in the past-which is further developed in the current paper. Recently, using a similar methodology, Dilli et al (2019) calculated a gender equality index for a collection of 129 countries during the period 1950-2003. They found that countries made substantial progress in gender equality over the past 50 years but that little convergence between countries could be observed.…”
Section: Introductionmentioning
confidence: 99%
“…Extending this line of research to a historical period, Perrin (2014) proposed a first attempt to measure the size of the gender gap in the past-which is further developed in the current paper. Recently, using a similar methodology, Dilli et al (2019) calculated a gender equality index for a collection of 129 countries during the period 1950-2003. They found that countries made substantial progress in gender equality over the past 50 years but that little convergence between countries could be observed.…”
Section: Introductionmentioning
confidence: 99%
“…For many European countries, elevating women’s status by reducing structural barriers has been a primary goal. The United Nations identified gender inequality as a key barrier to human development and has been measuring women’s status as a key component of the human development report for 25 years [ 42 ]. We draw upon a larger literature showing gender development at the country-level is associated with greater gender equality at the individual-level.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The progress of countries or territories to reduce the gender gap is essential to promote development (Adina, 2014) and positive social changes. Although inequality is obvious everywhere, its nature and degree are heterogeneous (Dilli, 2018). But it has a negative impact on the economies as well as in politics and social institutions (Agarwal, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In order to establish a concise diagnosis of gender inequality, we need to quantify its level by measuring the asymmetry either from the percentage gap or by establishing ratios between men and women. In this case, many organizations have proposed different types of gender indicators (Adina, 2014;Bericat, 2012;Dilli, 2018) to monitor the progress of public policies against discrimination. The European Institute for Gender Equality (EIGE) monitors progress in gender equity since 2013 through the Gender Equality Index (European Institute for Gender Equality, 2017) with 31 variables that are classified in six dimensions (work, money, knowledge, age, power, and health).…”
Section: Introductionmentioning
confidence: 99%